Motivation of physical education, health, and recreation students in carrying out movement activities after the Covid-19 transition period in Indonesia - Lokananta Teguh Hari Wiguno; Ari Wibowo Kurniawan; Febrita Paulina Heynoek; Usman Nasution; Mimi Haetami; Sudirman Sudirman; Hendra Jondry (CV Rezki Media, 2022)
The purpose of this study was to find out how far the motivation of Physical Education, Health, and Recreation (PEHR) students in Indonesia in carrying out physical activities during this transition period from two (2) years of no face-to-face learning by carrying out direct physical activity practices. The method used in this study is a survey by collecting data using questionnaires and questionnaires, as well as to analyze quantitative data used descriptive statistics, namely analysis of percentages and averages. The results of the study showed that the motivation of PEHR students to move after the transition from pandemic to endemic had positive results.